Studi Kelayakan Serat Tandan Kosong Kelapa Sawit Sebagai Penguat Komposit Untuk Aplikasi Lambung Kapal - Agus Mujianto; Hery Tri Waloyo (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The Republic of Indonesia is an archipelagic country, making ships an important means of transportation for inter-island crossings. Currently, ship hull construction still relies on fiberglass, which is not environmentally friendly. On the other hand, Indonesia is one of the world's largest producers of palm oil, leading to a significant amount of empty palm fruit bunches (EPFB) waste. If not utilized, this waste can cause environmental pollution. However, OPEFB fibers are now being used as a substitute for fiberglass in composite materials. Given the high demand for ships in Indonesia and the abundant supply of OPEFB fibers, research is needed to explore the potential of using OPEFB fibers as reinforcements in composites for ship hull construction. This study aims to investigate whether palm fruit bunch fibers can replace fiberglass in the shipbuilding industry. To determine the feasibility, the composite materials reinforced with EFB fibers need to be characterized. The properties to be examined in this research are the tensile strength and bending strength of the OPEFB fiber-reinforced composites with variations in fiber volume fraction and fiber length. The studied volume fractions are 20%, 30%, and 40%, while the fiber lengths are 4 cm, 6 cm, and 8 cm. The results show that the optimum volume fraction is 30% with tensile strength and bending strength of 12.35 MPa and 47.7 MPa, respectively. As for the fiber length, the best result is achieved with 8 cm length, yielding tensile and bending strengths of 13.3 MPa and 40.89 MPa, respectively. However, both tensile and bending strengths are still significantly below the minimum values required by the Indonesian Classification Bureau (BKI). Therefore, OPEFB fiber-reinforced composites are not suitable for ship hull construction.